Do N-Terminal Pro-C-Type Natriuretic Peptide Levels Relate to Severity of Preeclampsia? - (:unkn) unknown (HINDAWI LTD, 2020)
Aim. To compare the plasma N-terminal pro-C-type natriuretic peptide concentrations of normotensive pregnant women, patients with mild preeclampsia, and patients with severe preeclampsia. Methods. We collected venous blood samples from 25 normotensive pregnant women, 15 patients with mild preeclampsia, and 15 patients with severe preeclampsia. The women were at 30th to 40th weeks of gestation and in an age range of 20 to 35. The N-terminal pro-C-type natriuretic peptide levels were measured by ELISA. Statistical comparisons were made by one-way analysis of variance, Kruskal-Wallis, and Mann-Whitney U tests. Results. The median (interquartile range-IQR) values of the N-terminal pro-C-type natriuretic peptide were 6.48 (3.33) pmol/L in the normotensive women group, 7.37 (3.43) pmol/L in patients with mild preeclampsia, and 11.52 (6.13) pmol/L in patients with severe preeclampsia. The N-terminal pro-C-type natriuretic peptide was significantly elevated in the severe preeclampsia study group (P<0.001), whereas there was no significant difference between those with mild preeclampsia and the normotensive groups (P>0.05). Conclusion. Our data indicate that the plasma concentration of the N-terminal pro-C-type natriuretic peptide is significantly increased in patients with severe preeclampsia, but not in patients with mild preeclampsia. The severity of preeclampsia may be related to the circulating levels of the N-terminal pro-C-type natriuretic peptide concentrations.
Keywords: HYPERTENSION; PREGNANCY; SECRETION